2015
DOI: 10.1103/physreva.91.043614
|View full text |Cite
|
Sign up to set email alerts
|

Polar molecules in frustrated triangular ladders

Abstract: Polar molecules in geometrically frustrated lattices may result in a very rich landscape of quantum phases, due to the nontrivial interplay between frustration, and two-and possibly three-body intersite interactions. In this paper we illustrate this intriguing physics for the case of hard-core polar molecules in frustrated triangular ladders. Whereas commensurate lattice fillings result in gapped phases with bond order and/or density-wave order, at incommensurate fillings we find chiral, two-component, and pai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…At density r = 3 2 (r = 1 2 D ) the doublons minimize the energy by arranging themselves along the rungs of the figure 5(blue circles). Upon increasing ¢ t the system enters into the CSF phase, similarly as for the case of hardcore bosons [26]. The transition to the CSF phase at r = 1.5 is obtained by plotting the chiral order parameter.…”
Section: Gapped Phasesmentioning
confidence: 99%
See 1 more Smart Citation
“…At density r = 3 2 (r = 1 2 D ) the doublons minimize the energy by arranging themselves along the rungs of the figure 5(blue circles). Upon increasing ¢ t the system enters into the CSF phase, similarly as for the case of hardcore bosons [26]. The transition to the CSF phase at r = 1.5 is obtained by plotting the chiral order parameter.…”
Section: Gapped Phasesmentioning
confidence: 99%
“…In this paper, we will illustrate the nontrivial interplay between lattice occupation and frustration in these models for the particular case of ultra-cold atoms in zig-zag lattices(see figure 1). Zig-zag lattices are equivalent to one-dimensional lattices with nearestand next-nearest-neighbor hoppings, and have been extensively investigated in the presence of frustration [16][17][18][19][20][22][23][24][25][26]. They may be easily realized with ultra-cold atoms in optical lattices by superimposing incoherently a one-dimensional lattice and a triangular lattice, as shown in [23].…”
Section: Introductionmentioning
confidence: 99%
“…The most dominating interactions arise from the nearest-neighbour terms 42,43 , and also in optical lattice by adjusting the distance between sites, one can make other subdominating interactions quite smaller 43 . Thus, we restrict ourself to only nearest-neighbour terms of V (i, j) in the Hamiltonian 41 . The two body nearest-neighbour term, V (i, j), can be described as Since the dipolar interaction depends on angle and distance between the dipoles, it allows tuning of magnitude and sign of these interaction parameters to a wide range to explore rich quantum many-body phases.…”
Section: The Modelmentioning
confidence: 99%
“…In a recent experimental study on ultra-cold three dimensional optical lattice systems, effect of multi body interaction has been demonstrated 36,37 . Furthermore, in a few numerical studies, it was shown that dominant three body Coulombic interactions can give rise to a host interesting phases, like supersolid and bondorder phases [38][39][40][41] . Interestingly, for polar molecules in optical lattice, the realization of three-body interactions using microwave field have been proposed [44][45][46] and since then there have been various theoretical studies of microscopic models with three-body interactions [47][48][49][50][51] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation